Gesturing with Tangible Interfaces for Mixed Reality - Dias, J.; Pedro, S.; Bastos, R. (Proc Gesture Workshop 2003, The 5th International Workshop on Gesture and Sign Language based Human-Computer Interaction, Genova, Italy, 2003)
This work reports a Tangible Mixed Reality system that can be applied to interactive visualization scenarios in diverse human-assisted operations, such as in training, troubleshooting, and maintenance tasks of real equipments, or in product design scenarios in various sectors: Architecture, Automotive or Aerospace. With the system, the user is able to intuitively interact with an augmented version of real equipment, in normal working settings, where she can observe 3D virtual objects (in the VRML 97 format) registered to the real ones. Totally sensor-less Tangible Interfaces (Paddle and Magic Ring), are used to aid interaction and visualization tasks in the mixed environment. By means of Tangible Interfaces gesturing recognition, it is possible to activate menus, browse and choose menu items or pick, move, rotate, and scale 3D virtual objects, within the user’s real working area or transport the user from Augmented Reality to a fully Virtual Environment and back.